Environmental Accounting in Responding to the Deforestation Crisis in Indonesia : Perspective of Maqashid Shariah and Sustainability Reporting - Hidayah, Nur; Latif, Abdul; Alimuddin, Alimuddin (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine environmental accounting disclosure through the lens of Maqashid Shariah and sustainability reporting, emphasizing the role of spiritual values, ethical intentions, and moral responsibility in corporate accountability particularly in addressing the deforestation crisis. The object of analysis is the 2024 sustainability report of PT Triputra Agro Persada Tbk, Indonesia’s largest palm oil company with a significant deforestation footprint. The findings reveal that although the company presents various narratives of environmental and social commitment, the disclosure remains largely symbolic. It lacks quantitative data, measurable indicators, and verifiable environmental impacts particularly related to carbon emissions, land degradation, and conservation costs. No evidence was found of external environmental audits or written policies to protect indigenous communities, raising concerns over potential greenwashing. From the Maqashid Shariah perspective, especially concerning hifz al-bi’ah (environmental protection) and hifz al-nafs (protection of life), the sustainability report fails to reflect a deep moral and spiritual corporate responsibility. Environmental accounting, in this context, plays a crucial role in translating Islamic values into transparent, accountable, and transformative corporate disclosures. This study highlights the urgent need for more substantive sustainability reporting frameworks that integrate Shariah ethics and ecological accountability, enabling Islamic-based corporations to pursue sustainability not only for regulatory compliance or market legitimacy, but as a form of divine stewardship (amanah ilahiyah).